The Effect of Google Classroom on Learning Independence and Mathematics Learning Outcomes: A Case of SMKN 3 Kupang, Indonesia - Wangge, Magdalena (FKIP Universitas Lampung, 2022)
During the time of online learning is wrong One of the applications used in Google Classroom. The purpose of this study is to find out the effect of the use of Google Classroom on the independence of learning, use of Google Classroom for results learn mathematics, use Google Classroom independence of learning and learning outcomes of mathematics, as well as the influence between independence of learning on effects of study mathematics in students of State Vocational High School 3 Kupang. This research uses a type of quantitative research with survey methods. This study concludes that there is an influence on the use of Google Classroom on independence of learning, there is a significant influence on the use of Google Classroom, there is an influence on the use of Google Classroom on independence of learning and learning outcomes of mathematics, and there is an influence between the independence of learning on learning outcomes mathematics in students of State Vocational High School 3 Kupang.Keywords: google classroom, independence of learning, learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp152-161